2010
DOI: 10.1523/jneurosci.3228-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Paired Immunoglobulin-Like Receptor B Does Not Promote Axonal Plasticity or Functional Recovery after Traumatic Brain Injury

Abstract: The rewiring of neural networks is a fundamental step in recovering behavioral functions after brain injury. However, there is limited potential for axonal plasticity in the adult CNS. The myelin-associated proteins Nogo, myelin-associated glycoprotein (MAG), and oligodendrocyte myelin glycoprotein (OMgp) are known to inhibit axonal plasticity, and thus targeting the inhibitory pathways they participate in is a potential means of promoting plasticity and functional recovery. Each of Nogo, MAG, and OMgp interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 56 publications
(58 reference statements)
4
52
1
Order By: Relevance
“…The low levels of PirB protein expression in cortical cultures and in adult brain are consistent with a recent report indicating that CST or rubrospinal sprouting into the denervated spinal cord is not enhanced in PirB Ϫ/Ϫ mice after unilateral traumatic brain injury (27). Moreover, CST regeneration is not enhanced in PirB Ϫ/Ϫ mice after dorsal hemisection spinal cord injury (28).…”
Section: Discussionsupporting
confidence: 90%
“…The low levels of PirB protein expression in cortical cultures and in adult brain are consistent with a recent report indicating that CST or rubrospinal sprouting into the denervated spinal cord is not enhanced in PirB Ϫ/Ϫ mice after unilateral traumatic brain injury (27). Moreover, CST regeneration is not enhanced in PirB Ϫ/Ϫ mice after dorsal hemisection spinal cord injury (28).…”
Section: Discussionsupporting
confidence: 90%
“…Further, in sections of the cerebral cortex, the PIR-B-alkaline phosphatase fusion protein is detected in association with the cell bodies and dendrites of cortical pyramidal neurons. We also reported that corticospinal neurons expressed PIR-B (13). In addition, we found that interneurons associated with the BDA-labeled CST in the spinal cord were immunoreactive for PIR-B.…”
Section: Discussionsupporting
confidence: 66%
“…4, D and E). These results indicate that PIR-B may be expressed in the interneurons in the spinal cord as well as the pyramidal neurons in the cerebral cortex (7,13).…”
Section: Cst Regeneration After Sci Was Not Detectable In the Pir-bmentioning
confidence: 71%
“…However, another candidate receptor, paired immunoglobulin-like receptor B (PirB), has recently been identified [18]. Activation of PirB leads to inhibition of neural and axonal regeneration, but again, genetic deletion of PirB did not promote axonal plasticity and functional recovery in a mouse model of traumatic brain injury [19]. Taken together, those myelin-derived inhibitory molecules (Nogo/MAG/OMgp) and their receptors (NgR and PirB) negatively impact neurite extension, and therefore, those signaling pathways could be potential targets for axonal repairing and remodeling for CNS diseases.…”
Section: Triggers Of Axonal Degeneration and Neuronal Death In Cnsmentioning
confidence: 99%